2003
DOI: 10.5194/acpd-3-5357-2003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tethered balloon measurements of biogenic volatile organic compounds at a Boreal forest site

Abstract: Abstract. Measurements of biogenic volatile organic compounds (VOCs) were performed at Hyytiälä, a Boreal forest site in Southern Finland as part of the project OSOA (origin and formation of secondary organic aerosol) in August 2001. At this site, frequent formation of new particles has been observed and the role of biogenic VOCs in this process is still unclear. Tethered balloons served as platforms to collect VOC samples within the planetary boundary layer at heights up to 1.2 km above ground during daytime.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 21 publications
1
11
1
5
Order By: Relevance
“…The isoprene-to-MT carbon ratio was 15.3 § 7.2 during the campaign period. This ratio was close to those found in Amazonian rain forests (e.g., 15.2; Greenberg et al 2004) where NPF was not observed at the ground level, but much higher than 0.18 observed in the Finland boreal forest (Spirig et al 2004) where frequent NPF was observed.…”
Section: Measurementssupporting
confidence: 77%
“…The isoprene-to-MT carbon ratio was 15.3 § 7.2 during the campaign period. This ratio was close to those found in Amazonian rain forests (e.g., 15.2; Greenberg et al 2004) where NPF was not observed at the ground level, but much higher than 0.18 observed in the Finland boreal forest (Spirig et al 2004) where frequent NPF was observed.…”
Section: Measurementssupporting
confidence: 77%
“…Other pollutants, especially those that have implications for public health or ecosystems, have received less attention: for example, nitrogen oxides, NO x ; volatile organic compounds, VOCs; sulfur dioxide, SO 2 ; carbon monoxide, CO; and particulate matter, PM. In addition, not all sectors that contribute to local emissions in the Arctic were considered in previous assessments; for example, waste burning is not (Huang et al, 2015), (b) Evaluating the Climate and Air Quality Impacts of Short-Lived Pollutants version 5 (ECLIPSEv5; Stohl et al, 2015), and (c) Hemispheric Transport of Air Pollution version 2 (HTAPv2; Janssens-Maenhout et al, 2015) for the year 2010, from Sergent (2017). Note not all inventories cover the entire Arctic, hence the focus on Eurasia.…”
Section: Local Arctic Air Pollutant Emissionsmentioning
confidence: 99%
“…In the past years, it has been recognized that flaring linked to oil and gas extraction, particularly in northern Russia, is an important source of BC, suggested to be 66% of the total Arctic BC emissions (Stohl et al, 2013(Stohl et al, , 2015. More recent estimates suggest higher BC emissions from flaring activities in Russia (Huang et al, 2015;Huang & Fu, 2016) although note that estimates are very dependent on the emission factors used in different studies, for example, 1.6 g/m 3 of emitted gas in Stohl et al (2013) and 2.27 g/m 3 in Huang et al (2015).…”
Section: 1029/2018ef000952mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because tethered balloons have been used to quantify a variety of trace gas fluxes at the landscape scale [i.e. methane (Beswick et al, 1998;Choularton et al, 1995), non-methane hydrocarbons (Davis et al, 1994;Guenther et al, 1996;Greenberg et al, 1999;Spirig et al, 2004;Zimmerman et al, 1988), and carbon dioxide (Kuck et al, 2000)], employing quantitative radiometric instrumentation on such a platform opens new opportunities for comparing trace gas flux and spectral properties of vegetation at scales comparable to and larger than those measured by standard flux towers. Therefore, data acquired through platforms such as the SWAMI may be used to complement those data acquired through the tower-based Spectral Network (SpecNet) Working Group.…”
Section: Swami Platformmentioning
confidence: 99%